Neuropsychiatric Symptoms and Quality of Life in Patients With Adult-Onset Idiopathic Focal Dystonia and Essential Tremor - Lee, Sangjin; Chung, Sun Ju; Shin, Hae-Won (Frontiers in Neurology, 2020)
Background: While idiopathic focal dystonia (IFD) and essential tremor (ET) have been considered pure movement disorders, they reportedly induce neuropsychiatric manifestations and may thus be more accurately described as network disorders. Methods: The present multi-center, cross-sectional, case-control study evaluated the severity of depression and anxiety with the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI), respectively; the frequency of neuropsychiatric disorders with the Korean-Mini International Neuropsychiatry Interview; and QoL with the Short-Form 36 (SF-36). Results: Seventy-four subjects participated in this study (IFD, 27; ET, 24; controls, 23). The BDI and BAI scores were higher in the IFD and ET groups than in the control group. Although the frequency of neuropsychiatric disorders diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition Axis I was comparable among the groups, the prevalence of major depressive disorder tended to be high among patients with IFD. QoL was correlated with the severity of depression and anxiety across the groups. Conclusions: Depression and anxiety are more severe in patients with IFD and ET compared to healthy controls, while their severity is similar among patients with IFD and ET. Axis I major depressive disorder is relatively more prevalent in patients with IFD. Neuropsychiatric symptoms affect QoL regardless of the affected individual’s condition, addressing neuropsychiatric symptoms in patients with movement disorders may be crucial to improving their QoL.